Benthic foraminiferal growth seasons implied from Mg/Ca‐temperature correlations for three Arctic species. (22nd November 2016) - Skirbekk, Kari; Hald, Morten; Marchitto, Thomas M.; Junttila, Juho; Klitgaard Kristensen, Dorthe; Aagaard Sørensen, Steffen
Abstract: Core‐top sediment samples from Kongsfjorden, Svalbard, and adjacent fjord and shelf areas were collected in order to investigate a potential relationship between Mg/Ca‐ratios of Arctic benthic foraminifera and the ambient bottom water temperatures (BWT). The area is influenced by large seasonal variation in factors such as light and temperature, which is further strengthened by oceanographic shifts, including inflow of relatively warm Atlantic water. Four hydrological seasons have been defined. The studied samples were collected during the years 2005–2010 and comprise data from three hydrological seasons: spring, summer, and autumn. Five common species of cold‐water benthic foraminifera were investigated: Islandiella helenae/norcrossi, Buccella frigida, Nonionellina labradorica, Elphidium clavatum, and Cassidulina reniforme . For E. clavatum and C. reniforme, the investigations failed. For the remaining three species, the Mg/Ca‐temperature correlations initially appeared stochastic holding correlation coefficients between 0.01 and 0.15. However, grouping the data based on seasons gave stronger Mg/Ca‐temperature correlations, indicating specific growing seasons for the three species. The equations represent a starting point for a discussion on seasonality rather than robust, "ready‐to‐use" equations. I. helenae/norcrossi seems to reproduce and grow during summer (July/August) in outer Kongsfjorden. For B. frigida, a Mg/Ca‐temperature correlation is seen both in summer (July/August) and autumn (October/November) samples, indicative of a continuous reproduction/growth‐season lasting from July to November. N. labradorica appears to reproduce and grow during autumn (October/November). The results indicate that temperature reconstructions based on these benthic foraminifera reproduce seasonal temperatures rather than annual average temperatures. Key Points: Mg/Ca‐temperature correlation plots for three species of Arctic benthic foraminifera are presented The data set indicates season‐specific growth periods for the three species, which can be linked to specific events within the seasons Mg/Ca temperature reconstructions on these species represent seasonal temperatures rather than annual average temperatures in this area